Citation Indexing Revisited: Garfield’s Early Vision and Its Implications for the Future - Small, Henry (Frontiers in Research Metrics and Analytics, 2018)
Eugene Garfield’s ideas on citation indexing were gradually shaped over the course of the 1950s by his exposure to the thinking of various individuals such as J.D. Bernal, H.G. Wells, Chauncey Leake, William Adair and Joshua Lederberg. Two key concepts emerged during this early period which guided his later work: the importance of inter-disciplinary or cross-disciplinary research, and the notion that references could be used to index the documents they cited. These ideas were the basis for his landmark product the Science Citation Index. However, it took many years for the significance of his early insights to be appreciated and manifested in research studies and products. And in a real sense we continue to work out the implications of these ideas even today.